Effect of Planting Times and Methods of Rice (Oryza Sativa) on the Growth Period - Arabboevich, Ergashev Mukhammadjon; Akhramkhanovich, Mamakhanov Azizkhan (Researchparks Publishing, 2023)
The article provides information on the effect of rice on the growth cycles of the plant when planted at different times in the cultivation of rice as a secondary crop in different ways. Taking into account the soil and climatic conditions and biological characteristics of varieties in the country, the improvement of agro-techniques for quality cultivation of rice varieties, increasing rice yields, introduction of advanced technologies in the world, efficient use of each hectare is an urgent issue.